2017
DOI: 10.1007/s10661-017-6121-1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of honeys and flowers as soil element indicators

Abstract: Detection of soil element deficiencies is time consuming, requiring a major commitment for field work and analysis. Bees concentrate some elements in their honey which could allow soil element concentrations to be predicted without having to take large numbers of soil samples. We measured 14 element concentrations in soil, sunflower, acacia flower and honey samples from two different regions of Hungary. Across sites, the elements with significant correlation coefficients between honey and soil concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
3
2
Order By: Relevance
“…Contrary to studies on other honeys [ 13 , 50 ], there were no correlations between the elemental composition of mānuka honey and elemental concentrations in soils. The only soil factor that correlated with honey MGO was soil NO 3 − ( r = −0.88, p < 0.05) ( Figure 4 ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to studies on other honeys [ 13 , 50 ], there were no correlations between the elemental composition of mānuka honey and elemental concentrations in soils. The only soil factor that correlated with honey MGO was soil NO 3 − ( r = −0.88, p < 0.05) ( Figure 4 ).…”
Section: Resultscontrasting
confidence: 99%
“…Soil is the ultimate source of many elements in the floral nectar [ 13 , 14 ]. The concentration of elements in honey is affected by soil characteristics, and honey composition can be used for geographical discrimination or as a soil element indicator [ 13 , 15 , 16 , 17 ]. The response of L. scoparium to soil properties is cultivar-dependent [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Meister et al found no correlations between elemental concentrations in honey and soil in a set of mānuka honeys from New Zealand [ 15 ]. This is in contrast with studies from other geographical origins and floral sources [ 16 ].…”
Section: Introductioncontrasting
confidence: 86%
“…The soil as a reservoir of TEs represents a suitable indicator for the contamination of terrestrial environments. Nevertheless, according to our literature survey, minimal research has reported or even attempted to identify a linear relationship between TE contents in soil and in bees and their products (Czipa et al, 2017;Kastrati et al, 2021;Rashed et al, 2009;Zarić et al, 2017). This lack of studies may be due to the complexity of the system soil → plant → bee → bee products, where multiple factors, transport pathways, and sources of TEs are expected.…”
Section: Introductionmentioning
confidence: 95%
“…Unfortunately, the sensitivity and detection capability of a biomonitor are usually poorly defined (at best) compared with instrumental techniques employing, for example, a signal‐to‐noise concept. Furthermore, a biomonitor's ability to detect environmental pollution is frequently related to categorical variables (Di Fiore et al, 2022; Dżugan et al, 2018; Gutiérrez et al, 2015; Lambert et al, 2012; Perugini et al, 2011), yet reference to continuous variables (Costa et al, 2019; Czipa et al, 2017; Goretti et al, 2020; Rashed et al, 2009) should be preferred. The performance of a biomonitor has been largely deduced from hives kept at sites of different land use, where industrialized and urban areas had been expected to exhibit higher levels of pollution than their natural and rural counterparts (Ćirić et al, 2021; Dżugan et al, 2018; Sadowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%